The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1001/jamacardio.2017.0911
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to High-Intensity Statins Following a Myocardial Infarction Hospitalization Among Medicare Beneficiaries

Abstract: Many patients filling high-intensity statins following a myocardial infarction do not continue taking this medication with high adherence for 2 years postdischarge. Interventions are needed to increase high-intensity statin use and adherence after myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 13 publications
8
60
0
1
Order By: Relevance
“…In a recent study by Jia et al, post-PCI patients randomly assigned to more frequent follow-up visits with a physician had higher rates of medication adherence (56 vs. 46%, p < 0.001), as well as lower rates of MACE, than those assigned to the “usual care” group [41]. Supporting this finding, visiting with a cardiologist after MI discharge has been associated with 10–20% higher adherence to high-dose statin therapy at 6 months as well as similarly increased rates of persistence at 2 years [34]. Timing may be important in light of the observation of an association between patients who visit a provider within 6 weeks of MI discharge and a 5–10% higher (in absolute terms) adherence to post-MI therapies both short and long term [42•].…”
Section: Health Team and System-related Factorsmentioning
confidence: 91%
See 2 more Smart Citations
“…In a recent study by Jia et al, post-PCI patients randomly assigned to more frequent follow-up visits with a physician had higher rates of medication adherence (56 vs. 46%, p < 0.001), as well as lower rates of MACE, than those assigned to the “usual care” group [41]. Supporting this finding, visiting with a cardiologist after MI discharge has been associated with 10–20% higher adherence to high-dose statin therapy at 6 months as well as similarly increased rates of persistence at 2 years [34]. Timing may be important in light of the observation of an association between patients who visit a provider within 6 weeks of MI discharge and a 5–10% higher (in absolute terms) adherence to post-MI therapies both short and long term [42•].…”
Section: Health Team and System-related Factorsmentioning
confidence: 91%
“…This likely explains why prescription drug coverage has previously and, in recent literature, continues to be positively associated with medication adherence. In contrast, a lack of medication coverage is negatively associated with adherence [3234]. Consistent with these observations, Choudhry et al demonstrated that eliminating copayments for medications resulted in a 4–6% absolute increase in rates of medication adherence ( P < 0.001) [35].…”
Section: Socioeconomic Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…At 182 and 730 days after discharge, 54.8% and 36.7% of beneficiaries, respectively, remained on high‐intensity statins with high adherence. Whites, beneficiaries with fewer comorbidities, low‐income subsidy, and a high‐intensity statin fill prior to their MI and those who had cardiac rehabilitation and cardiologist visits post‐MI were more likely to remain on high‐intensity statins with high adherence …”
mentioning
confidence: 99%
“…However, as the authors themselves concede, their results are somewhat dependent on how they define discontinuation, reinitiation, and persistence—definitions which are not consistent throughout the literature. 12,15 More concerning is the large number of patients excluded by the current analysis. From an initial sample of >900 000 patients, >500 000 were excluded for not having comprehensive Medicare coverage (A+B+D−Health Maintenance Organization).…”
mentioning
confidence: 99%